Role of Active Center and Lysine Binding Sites of Plasmin in Plasmin-Induced Platelet Activation and Disaggregation - Lu, He; Soria, Claudine; Li, Hong; Soria, Jeannette; Lijnen, H Roger; Perrot, Jean Y; Caen, Jacques P (Thrombosis and Haemostasis, 1991)
Previous studies have shown that plasmin can activate platelets and - can also disperse platelet aggregates by degradation of fibrinogen bound to platelets. In this study, the role of the active center and the lysine binding sites (LBS) of human plasmin in activating platelets and in dispersing platelet aggresates is investigated using aprotinin and the tripeptide Val-Phe-Lys-CH2Cl to inhibit the active center and using epsilon-aminocaproic acid (EACA) to specifically block the LBS. Our results show that the catalytic activity of plasmin is indispensable both for activating platelets and for dispersing platelet aggregates. Binding of plasmin to platelets through the LBS enhances its activating potential, since both EACA (1 mM) and Lys-plasminogen (molar ratio of plasminogen:plasmin at 2:l to 4:1) inhibit plasmininduced platelet activation, whereas Glu-plasminogen at a molar ratio of 15: I had no effect. Furthermore, plasmin which lacks the LBS (miniplasmin), is about 3 fold less effective in activating platelets. Flowever, plasmin binding through the LBS is not absolutely required to disperse platelet aggregates, since EACA at 30 mmol/l was unable to prevent disaggregation by plasmin (half disaggregation time: 40 min in the presence of EACA against 27 min in its absence). It also appeared that fibrinogen receptors on activated platelets are resistant to plasmin degradation, and that disaggregation of plasmin-induced platelet aggregates was much slower than the degradation of fibrinogen by plasmin.